Detection of Shiga toxins, intimin and enterohemolysin in Escherichia coli strains isolated from children in eastern Slovakia - Liptáková, A; Siegfried, L; Podracká, L; Sabol, M; Sehnálková, H; Bogyiová, E; Rosocha, J; Kmetová, M; Kerestesová, H; Kotulová, D (Folia microbiologica, 2002)
Fifty Escherichia coli strains isolated from stool samples of 51 healthy children, 143 strains isolated from stool samples of 327 children with diarrhea and 24 strains isolated from stool samples of 21 children with suspected hemolytic uremic syndrome were examined for the presence of Shiga toxin-producing E. coli virulence factors (shiga toxin 1 and 2, intimin and enterohemolysin) and their genes. Vero-cell assay and latex agglutination were used for detection of Shiga toxin 1 and 2, TSB agar with washed erythrocytes was used for detection of enterohemolysin; genes encoding shiga toxin 1 and 2, intimin and enterohemolysin were detected using multiplex PCR. The presence of E. coli strains harboring genes encoding shiga toxin 1 and 2 (12 strains), intimin (34 strains) and enterohemolysin (12 strains) was demonstrated.
Keywords: infekce vyvolané Escherichia coli; Escherichia coli Infections; proteiny z Escherichia coli; feces; Humans; dítě; Child; hemolyziny; Escherichia coli; shiga toxiny; Shiga Toxins; lidé; bakteriální adheziny; Escherichia coli Proteins; Slovakia; Slovenská republika; transportní proteiny; Feces; předškolní dítě; Carrier Proteins; Hemolysin Proteins; polymerázová řetězová reakce; Polymerase Chain Reaction; Adhesins, Bacterial; Child, Preschool